The economics of microfinance - Armendáriz, Beatriz (MIT Press, 2007)
The book provides an overview of microfinance by addressing a range of issues, including lessons from informal markets, savings and insurance, the role of women, the place of subsidies, impact measurement, and management incentives. It integrates theory with empirical data, citing studies from Asia, Africa, and Latin America and introducing ideas about asymmetric information, principal-agent theory, and household decision making in the context of microfinance.